Mental Psychology of Voters: Social Media Marketing, Corporate Social Responsibility and Political Campaigns Perspectives - Rizgar Abdullah Saeed, Shiva Ilkhanizadeh (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This study examines how the psychological behavior of voters, voter attitudes, and voters’ actions respond to situations involving the use of a series of social media marketing, corporate social responsibility, and political campaign activities. It also investigates the mediating consequences of political campaigns on the mental psychology of voters. Questionnaires were electornically administered among university students in the Kurdistan region of Iraq. In conjunction with SPSS and AMOS version 24, the structural equation modeling approach was utilised to examine the relationships between the modeled variables on the basis of data collected from 525 university students. The reliability and validity of the measurements was confirmed before the proposed research hypotheses were tested using confirmatory factor analysis. The results revealed that social media marketing positively influences political campaigns, corporate social responsibility, and thee mental psychology of voters. CSR, political campaigns, and social media marketing's positive effects on mental psychology of voter have been supported. The results also confirmed that political campaigns significantly mediate the relationship between social media marketing and mental psychology of voters as well as the relationship between CSR and mental psychology. This study enriches the understanding of social media marketing, CSR activities, and political campaigns voter vis-à-vis the mental psychology of university students. Political groups can gain benefits by understanding how specific CSR activities can influence voter’s mental psychology and social media engagement value, leading to enhanced mental psychology and choices. The study's originality and novelty are embedded in its ability to build an integrated model that examines the interaction between social media marketing and mental psychology related to voters among university students. This study investigates the effects of social media marketing on the relationship between CSR activities, political engagement, and mental psychology of voters, which has been lacking a full investigation in the tertiary institutions' literature.